Hubungan Lingkungan Belajar di Sekolah dengan Motivasi Belajar IPA Siswa Kelas V SD - rosmalah, rosmalah; Amran, Muhammad; Cahyani, Indah Gita (Universitas Negeri Makassar, 2022)
The problem in this study is that there is still a school environment that is not good physically, socially and academically so that it affects students' learning motivation. This study is a quantitative study with a correlation design that aims to determine the relationship between the learning environment in schools and the motivation to learn science for fifth grade students of SD Gugus XXII, Lilirilau District, Soppeng Regency. The results showed that there was a significant relationship between the learning environment at school and the science learning motivation of fifth grade students of SD Gugus XXII, Lilirilau District, Soppeng Regency with a t-count value (4.3143) greater (>) t table value (1.67469) which means H0 rejected and H1 accepted. Based on the analysis of the data above, it can be concluded that the learning environment in schools has an impact on students' motivation to learn science in the classroom. So, the better the learning environment at school, the better the students' motivation to learn science. From these conclusions, the impact resulting from this research is known that a good learning environment in schools will increase students' motivation to learn science.